Eksplorasi Peran Robotic Process Automation (RPA) Dalam Akselerasi Efisiensi Akuntansi - Sukmawati Sukmawati; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The digital transformation of accounting has intensified the need for efficiency, accuracy, and adaptability in financial processes. This study aims to explore the role of Robotic Process Automation (RPA) in accelerating accounting efficiency through a qualitative, non-empirical approach based on a systematic literature review. The analysis synthesizes findings from relevant academic sources to construct a conceptual understanding of how RPA contributes to operational performance and information quality. The results indicate that RPA enhances efficiency by automating rule-based processes, improving data consistency, and reducing operational variability. Furthermore, the implementation of RPA enables a shift in professional focus from routine administrative tasks to analytical and strategic functions, thereby increasing the value contribution of accounting practices. The study also highlights that the success of RPA adoption is contingent upon organizational readiness, including governance structures, technological integration, and human capital capabilities. These findings suggest that RPA serves as a strategic enabler of sustainable efficiency in accounting.